The Development of Authentic Assessment Instrument of Hajj Manasik Practices of IX Grade of SMP PGRI 10 Candi in Sidoarjo Regency - Ajib Shofwanthoni, M.; Ridlo, Saiful; Elmubarok, Zaim (Universitas Negeri Semarang, 2019)
The objective of this study is to develop authentic assessment instruments for Hajj manasik that are valid, reliable, and practical in IX grade of the SMP PGRI Candi. This research was a development research with Borg & Gall model without stages of dissemination and implementation. The validity of the contents of the instrument was tested on four experts in their fields. The score given by the expert was calculated using the V Index to determine the value of its validity and with the ICC to find out the reliability score. The instrument was tested on 100 students, construct validity with Exploratory Factor Analysis (EFA), and reliability with alpha cronbach. The results obtain that 27 valid items from expert validation with the reliability of 0.824. Construct validity obtained KMO score of 0.812 with a significance of 0.000, while the value of MSA> 0.5 for 27 items that form 2 factors in accordance with the dimensions of Hajj manasik. Practical test, from 3 teacher respondents stated that it is practical to be used with a score of> 50%.